Aerobic exercise improves hippocampal function and increases BDNF in the serum of young adult males - Kelly, Aine; O'Mara, Shane (My University, 2011)
Physical activity has been reported to improve cognitive function in humans and rodents, possibly via a brain-derived neurotrophic factor (BDNF)-regulated mechanism. In this study of human subjects, we have assessed the effects of acute and chronic exercise on performance of a face-name matching task, which recruits the hippocampus and associated structures of the medial temporal lobe, and the Stroop word-colour task, which does not, and have assessed circulating concentrations of BDNF and IGF-1 in parallel. The results show that a short period of high-intensity cycling results in enhancements in performance of the face-name matching, but not the Stroop, task. These changes in cognitive function were paralleled by increased concentration of BDNF, but not IGF-1, in the serum of exercising subjects. 3 weeks of cycling training had no effect on cardiovascular fitness, as assessed by VO2 scores, cognitive function, or serum BDNF concentration. Increases in fitness, cognitive function and serum BDNF response to acute exercise were observed following 5 weeks of aerobic training. These data indicate that both acute and chronic exercise improve medial temporal lobe function concomitant with increased concentrations of BDNF in the serum, suggesting a possible functional role for this neurotrophic factor in exercise-induced cognitive enhancement in humans.
PUBLISHED
Keywords: Neuroscience; Physiology; brain-derived neurotrophic factor (BDNF); Neuroscience